504 Integration of evidence into practice and policy in state health departments in the United States. (1st September 2016) - Marr, Angela
Abstract : Background: The Centres for Disease Control and Prevention's (CDC) National Centre for Injury Prevention and Control (NCIPC) empowers states to take action to protect residents and put an end to violence and injuries. NCIPC provides critical funding and technical assistance through its Core Violence and Injury Prevention Program (Core VIPP). The program helps strengthen state capacity to collect and use data to better understand local injury environments and challenges, plan injury prevention and control efforts, and carry out and evaluate life-saving interventions. The Core VIPP modestly funds 20 state health departments at 250, 000 annually. In order to achieve health impact with limited resources, state health departments strategically utilise implementation partners and evidence based strategies. Methods: The Core VIPP promotes the use of the best available evidence through an annual evaluative review process. Proposed state strategies are compared against a collection of evidence-based registries and emerging evidence compiled by subject matter experts. The best available evidence review findings are shared interactively with state practitioners. Technical assistance is provided to support continuous quality improvement and alignment with evidence. The evaluative review was initiated in Year 1 of a 5-year program and repeated annually. Results: In Year 3 of the program, 72% of all state strategies were deemed to be based on the best available evidence in the field. This is up from 59% in Year 1 and moving towards a 5-year goal of 80% of all implemented strategies. Conclusions: These findings provide support for continuing the use of the annual state strategy evaluation. Through technical assistance, rapid feedback and continuous quality improvement, the program was able to increase the number of impactful strategies implemented at the state level.